Short Communication: Estimation of the above- and below-ground carbon stocks in University of Lampung, Indonesia - IRWAN SUKRI BANUWA; RIZKI AFRILIYANTI; MUHAJIR UTOMO; SRI YUSNAINI; MELYA RINIARTI; PURBA SANJAYA; ERDI SUROSO; WAHYU HIDAYAT (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Banuwa IS, Afriliyanti R, Utomo M, Yusnaini S, Riniarti M, Sanjaya P, Suroso E, Hidayat W. 2019. Short Communication: Estimation of the above- and below-ground carbon stocks in University of Lampung, Indonesia. Biodiversitas 20: 676-681. University of Lampung in Indonesia has been promoting green campus program since 2004 to meet environmental goals, including specific targets for energy and CO2 reductions. This study was conducted to establish baseline data on the carbon stock and carbon sequestered in the campus of University of Lampung in order to support the program. The above-ground carbon stocks were estimated from tree biomass, understory biomass, and litters, while under-ground carbon stocks were measured by determining the organic carbon in soil. The results showed that the average above-ground carbon stock was 35.65 t.ha-1, consisted of 35.10 t.ha-1, 0.18 t.ha-1, and 0.12 t.ha-1 from trees biomass, understory biomass, and litters, respectively. The average below-ground carbon stock was 317.33 t.ha-1 and the CO2 uptake by plants was 130.74 t.ha-1. The Faculty of Agriculture with the largest area of green open space contributed to the highest carbon stocks and carbon sequestration, while the Faculty of Medicine showed the lowest values. The results could be essential to suggest the climate change mitigation effort, such as the expansion and optimization of green spaces area.